Hybrid electric vehicles take to the streets. - Hermance, D.
In this paper, the authors describe how, equipped with a gasoline engine and an electric motor, hybrid electric vehicles can now bridge the gap between vehicle range and environmental concerns
Keywords: Electric motor; Environmental concerns; Gasoline engine; Hybrid electric vehicles; Vehicle range